Peningkatan Pemahaman Literasi Digital pada Pemuda Desa Sanahu - Ronald Darlly Hukubun; Intan Telussa; Breandly Daud Zefanya Selly; Musa Geretz Tilukay; Natachya Batseba Bernard (Lembaga Pengembangan Kinerja Dosen, 2026)
Digital literacy is a fundamental ability for the younger generation in facing increasingly rapid technological developments. However, youth in Sanahu Village still experience limited internet access which has an impact on low mastery of digital literacy. This condition not only increases their vulnerability to the spread of misinformation, but also limits their participation in education, employment opportunities, and technology-based social activities. In response to these problems, the service team implemented a digital literacy education program that focuses on improving critical thinking skills, digital ethics, and the ability to utilize technology productively. This activity was held on October 23, 2025 at the Elim Church Building – Sanahu Village by involving 50 young men and women as participants. The implementation method includes material delivery, interactive discussions, and evaluation of understanding through simple assessment instruments. The results of the evaluation showed a significant increase in participants' understanding of the concept of digital literacy, including the ability to identify credible information and practice media ethics. These findings confirm that digital literacy education has a strategic role in empowering youth and supporting the development of Sanahu Village towards a more adaptive, critical, and competitive society in the digital era.